The Quality-Weighted Matching Function: Did the German Labor Market Reforms Trade-Off Efficiency against Job Quality? - Hermann Gartner; Thomas Rothe; Enzo Weber (Journal of Money, Credit and Banking, 2023)
We evaluate the quantity–quality trade-off on the labor market by estimating an augmented matching function weighting the matches by quality measures. We use the approach to evaluate the German labor market reforms conducted between 2003 and 2005. Indeed, we find a significant quantity–quality trade-off. However, even after controlling for job quality, a good half of the positive effect of the reforms on matching efficiency~remains.
Keywords: 330; matching approach; quantity–quality trade-off; labor market reforms; Germany